(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study was aimed towards finding the prevalence of non strabismic binocular vision dysfunctions (NSBVD) in the Indian population presenting with different symptoms pertaining to binocular vision disorders. Method: This retrospective study included one hundred and sixty one patients who presented to the out- patient department with symptoms of binocular vision dysfunction, during a period of one year. Patients were in the age group of 18 ±6.93, with 71 males and 90 females. Their binocular vision dysfunction was assessed via several diagnostic modules/tools designed for binocular vision assessment. Results: Results indicate that the most common binocular vision anomalies in this studied population are fusional vergence dysfunction with accommodative infacility (40.38%), convergence insufficiency with accommodative infacility (24.36%), Fusional vergence dysfunction (7.05%). Convergence Insufficiency and Accommodative infacility showed the same prevalence of 7.7%. Discussion: Accommodative and non strabismic binocular vision dysfunctions are commonly underdiagnosed/undiagnosed in clinical practice. These disorders affect academic performance, sports activities and general quality of life. An appropriate detailed orthoptic examination and accurate diagnosis is necessary to manage these binocular vision dysfunctions.